Furan Dissociation Induced by Collisions with H3+ and C+ Ions - Tomasz J. Wasowicz (Molecules, 2025)
Ion interactions with molecular structures give insights into physicochemical processes in the cosmos, radiation damage, plasma, combustion, and biomass conversion reactions. At the atomic scale, these interactions lead to excitation, ionization, and dissociation of the molecular components of structures found across all these environments. Furan, cyclic aromatic ether (C4H4O), serves as a gas-phase deoxyribose analog and is crucial for understanding key pathways in renewable biomass conversion, as its derivatives are versatile molecules from lignocellulosic biomass degradation. Therefore, collisions of H3+ and C+ ions with gas-phase furan molecules were investigated in the 50–1000 eV energy range, exploiting collision-induced emission spectroscopy. High-resolution fragmentation spectra measured at 1000 eV for both cations reveal similar structures, with C+ collisions resulting in more significant furan fragmentation. Relative cross-sections for product formation were measured for H3+ + C4H4O collisions. Possible collisional processes and fragmentation pathways in furan are discussed. These results are compared with those for tetrahydrofuran and pyridine to illustrate how the type and charge of the projectile influence neutral fragmentation in heterocyclic molecules.